Clinical Features and Predictors of Dysplasia in Proximal Sessile Serrated Lesions - Yi Yuan Tan; Gary Sei Kiat Tay; Yu Jun Wong; James Weiquan Li; Andrew Boon Eu Kwek; Tiing Leong Ang; Lai Mun Wang; Malcolm Teck Kiang Tan (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims Proximal colorectal cancers (CRCs) account for up to half of CRCs. Sessile serrated lesions (SSLs) are precursors to CRC. Proximal location and presence of dysplasia in SSLs predict higher risks of progression to cancer. The prevalence of dysplasia in proximal SSLs (pSSLs) and clinical characteristics of dysplastic pSSLs are not well studied. Methods Endoscopically resected colonic polyps at our center between January 2016 and December 2017 were screened for pSSLs. Data of patients with at least one pSSL were retrieved and clinicopathological features of pSSLs were analysed. pSSLs with and without dysplasia were compared for associations. Results Ninety pSSLs were identified, 45 of which had dysplasia giving a prevalence of 50.0%. Older age (65.9 years vs. 60.1 years, p=0.034) was associated with the presence of dysplasia. Twelve pSSLs were 10 mm or larger. After adjusting for age, pSSLs ≥10 mm had an adjusted odds ratio of 5.98 (95% confidence interval, 1.21-29.6) of having dysplasia compared with smaller pSSLs. Conclusions In our cohort of pSSLs, the prevalence of dysplasia is high at 50.0% and is associated with lesion size ≥10 mm. Endoscopic resection for all proximal serrated lesions should be en bloc to facilitate accurate histopathological examination for dysplasia as its presence warrants shorter surveillance intervals.